(untitled) - Kottak, Conrad Phillip (Boston, 2006)
This concise text offers both a serious scientific introduction to physical anthropology and archaeology and a holistic approach to the course. Interspersed through it, innovative "Bringing It All Together" essays show how anthropology’s subfields and dimensions combine to interpret and explain a common topic. In addition, every new copy of the second edition is packaged free with a new student CD-ROM!
Keywords: Physical anthropology,Archaeology,Anthropology, Prehistoric,Nhân loại học thể chất,Khảo cổ học